Hypocholesterolemia and Inflammatory Biomarkers Act as Predictors of Severe Vitamin D Deficiency in Patients With Crohn’s Disease: A Clinical Analysis of 862 Patients in China - Lu, Jie; Yu, Fei; Huang, Jun; Yu, Haitao; Li, Fengying; Le, Zhi’an; Cheng, Yulan; Zhang, Qi; Li, Guiling; Xie, Xinyou; Tang, Huifang; Zhang, Jun (Frontiers in Nutrition, 2022)
Abstract Background: In this study, we enrolled 862 Crohn’s disease (CD) patients in China to investigate the correlation between serum vitamin D (SVD) and serum lipids, inflammatory biomarkers and important clinical parameters. Materials and Methods: 25(OH)D was measured by LS/MS. Correlation analysis, chi-square tests and logistic regression analysis were performed to determine the correlations between vitamin D and potential risk factors when vitamin D levels were lower than 10 ng/mL or lower than 20 ng/mL. Results: The incidence of severe vitamin D deficiency (SVD<10 ng/mL) in CD patients was significantly higher than that in healthy controls (28.9% vs 9.5%). Multinomial logistic regression analysis showed that penetrating disease ((odds ratio (OR) = 2.18), low levels of high-density lipoprotein cholesterol (HDL) (OR = 1.91), high erythrocyte sedimentation rate (ESR) (OR = 1.73) and platelet count (PLT) (OR = 2.71) were regarded as predictors of severe vitamin D deficiency, while only PLT (OR=1.90) and HDL (OR=1.76) were considered as predictors of mild vitamin D deficiency (SVD 10-20 ng/mL). Conclusion: Our results confirm a higher incidence of severe vitamin D deficiency in CD patients in China, and show that vitamin D deficiency would be could result from the combined effects of penetrating disease, inflammation and low levels of HDL.